Psychosocial predictors of substance abuse among adolescents - Pretorius, Charmaine (University of the Free State, 2002)
A review of the literature indicates that the etiology of substance abuse amongst adolescents is still largely unclear. It is, however, generally accepted that the cause is usually not due to a single variable, but rather to a complex interaction between intrapersonal and interpersonal factors. The goal of this study was to determine whether there is a difference between substance-abusing adolescents and non-using adolescents with regard to the mentioned factors. A multicultural group of 302 Grade 11 learners completed questionnaires to assess these characteristics: a biographical questionnaire, the NEO Personality Inventory, the Adolescent SASSI-A2 and the Fortitude Scale. The various characteristics of these adolescents were compared concerning the three levels of substance use, namely low probability of use, abuse and dependence on substances. Significant differences in the mean scores concerning agreeableness, conscientiousness, setï-eppreiset, family support and general social support in the three levels of substance use groups were found. The results are discussed, the shortcomings of the study indicated and recommendations made.

'n Oorsig van die literatuur dui aan dat die etiologie van substansmisbruik onder adolessente nog grootliks onduidelik is. Dit word egter algemeen aanvaar dat die oorsaak gewoonlik nie aan 'n enkele veranderlike toegeskryf kan word nie, maar eerder aan 'n komplekse interaksie tussen intrapersoonlike en interpersoonlike faktore. Die doel van hierdie studie was om te bepaal of daar 'n verskil bestaan tussen adolessente wat substanse misbruik en diegene wat nie substanse misbruik nie, en wel ten opsigte van die genoemde faktore. 'n Multikulturele groep van 302 Graad 11 leerders het vraelyste voltooi ten einde hierdie eienskappe te assesseer: 'n biografiese vraelys, die NEO Persoonlikheidsvraelys, die Adolessente SASSI-A2 en die Fortaliteitskaa/. Die onderskeie eienskappe is vergelyk rakende die drie vlakke van substansgebruik, naamlik lae waarskynlikheid van gebruik, misbruik en afhanklikheid van substanse. Betekenisvolle verskille is gevind ten opsigte van die drie vlakke substansgebruik en wel ten opsigte van welgevalligheid, pligsgetrouheid, selfbeoordeling, gesinsondersteuning en algemene sosiale ondersteuning. Die resultate word bespreek, leemtes van die studie aangedui en aanbevelings gemaak.
Dissertation (M.Soc.Sc. (Counselling Psychology))--University of the Free State, 2002
Keywords: Alcohol abuse; Substance abuse; Psychosocial predictors; Adolescents; Intrapersonal factors; Interpersonal factors; Fortitude; NEO Personality Inventory; Adolescent SASSI-A2; Fortitude Scale; Drug abuse -- Forecasting; Drug abuse -- Social aspects